Uma análise histórica da visão de anormalidade em Freaks (1932), de Tod Browning - Rodrigues, Lorrane Campos [UNIFESP] (2020)
This study has as object the movie Freaks, directed in 1932 by Tod Browning, and investigate the representation of abnormality. The movie it is a free adaptation of the tale, Spurs (1917, Tod Robbins and tells the story of the involvement between two characters who live and work in a circus: a midget named Hans and a trapeze artist named Cleopatra and their relation in with the other artists of the troupe. Bringing in its plot the theme of the human body and the parameters of physical abnormality, the film was the target of several criticisms for its content, being removed from circulation a few months after the premiere. We believe that there is a narrative instability in the representation of these bodies. Despite the plot building positive actions on the freak characters, there are multiple representations in these deformed bodies and this makes it difficult to perceive who is the abnormal. These freak representations in the movie are based on forms of social perception about these people, based not only on the eugenic scientific debate of the late 19th century, early 20th century, but also on representations of the characters based on manifestations of American popular culture (freak show presentations). Therefore, the gaze is in a manifestation of crisis in front of these bodies, because there are a number of overlapping representations.